Strategies for Improving Visual Inspection Performance - Jerry L. Purswell; LaVerne L. Hoag (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 1974)
This paper summarizes recent results obtained in inspection studies including several studies performed by the authors. Both static and dynamic visual inspection tasks are included. Based on these results, a proposed new integrated design procedure for inspection tasks that will approach the optimal design has been formulated. The review of recent research results includes the following primary variables: the speed of the item passing the inspector, the spacing of items, the percentage of defective items, the illumination level, the contrast between the item being inspected and the background, and the effectiveness of individual versus group inspection. The authors have used their research results in combination with the results in the literature to formulate new integrated procedures for designing inspection stations and job procedures. The authors have also analyzed the effects of inspector performance on the overall quality control plans already in use in industry. The economic effects of changes in inspector performance which result from redesign of the inspection task are then demonstrated as a part of the overall design procedure.